The Duties & Authorities of Land Deeds Officer (PPAT) in Implementing the First Land Registration - Agus Nuryanto; Setyawati Setyawati; Achmad Arifullah (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
The purpose of this study is to find out and analyze how the Duties and Authorities of Land Deed Maker Officials in the Implementation of Land Registration for the first time. To find out and analyze the Constraints and Solutions of Land Deed Making Officials in carrying out land registration activities for the first time and to find out what efforts must be made by PPAT. The method used by the researcher is Empirical Jurisdiction and The specifications in this study include descriptive analysis. The sources and types of data in this study are secondary data obtained from library studies. Based on the results of the study that The Duties and Authorities of the Land Deed Making Official in the Implementation of Land Registration for the first time are:make an authentic deed that plays a role in providing juridical data on changes to data on the implementation of land registration.The obstacles are: a.The inability of the parties to complete the requirements related to taxation. b.For the first application for land registration with proof of land acquisition in the form of a sale and purchase receipt or sale and purchase receipt, but the evidence in the form of a sale and purchase seal or sale and purchase receipt has been damaged. c. Requirements relating to taxation. d. Lost and unknown land book in the Land Office. The solution: a. The requirements that must be met by applicants who wish to apply for land registration are incomplete for the first time. b. Ask for a copy to the local Village Office, because all data on the sale and purchase of the land is in the Village office. c. All land owners are required to pay Land and Building Tax regularly every year if they want to register their land rights. d. It is hoped that people who have land that have not been registered (certified) to register their land with the Regency/Municipal National Land Agency Office regarding the importance of registering land rights.